Library Services in Supporting the Curriculum According to the National Standards of Library at Elementary School - Damayanti, Era Valentina; Suharso, Putut (Edulib, 2022)
This study aims to describe the implementation of the national library standard, especially the point of integration of the school library with the curriculum at SDIT At-Taqwa Surabaya, and the relationship between these standards and the satisfaction of the user community. This research is a qualitative method based on case studies. Data collection using observation, semi-structured interviews, and literature studies that take the subject from the SDIT At-Taqwa Library Surabaya. Researchers used purposive sampling to select informants with criteria relevant to the research objectives so that the librarian suitable became an informant. This finding explains that the eight points in integrating elementary school libraries with the curriculum based on SNP 10:2017, are half relevant to the existing standard. Meanwhile, the other four points still do not conform with the current standards because several reasons influence them. Future research is expected to be able to review aspects of elementary school library integration with the curriculum in the National Library Standards for the coming year and its relationship to user community satisfaction.